Deepsthambh with niches - Ghosh, Ayan (2023)
Deepstambhas (lamp pillars) form a distinct feature of Hindu temple architecture in Maharashtra and Goa. The deepstambhas at Walkeshwar were earlier used for illumination purpose during Deepavali and other important Hindu festivals, like Dussehra and Shivratri. A person would climb the deepstambhas and place diyas on the extended branches or in small niches. Over time, the practice has been discontinued at Walkeshwar and the deepstambhas now serve as resting place for pigeons.